Lessons Learned in Research and Development With Porcine Livers and the Clinical Translation—Beating the Organ Clock With Normothermic Machine Perfusion - Schuler, Martin Jörg; Becker, Dustin; Machacek, David; Kalt, Fabian; Fröhlich, Rafael; Lopez‐Lopez, Victor; Onder, Christopher; Oberholzer, Jose; Eshmuminov, Dilmurodjon (Clinical transplantation, 2025)
ABSTRACT Short‐term (less than 24 h) normothermic liver perfusion devices are currently used in clinical practice. They improve logistics, simplify recipient matching, and aid in transplant decisions. At the same time, researchers globally are actively working on technologies to extend organ preservation times, mainly for transplantation. This paper investigates what it takes to keep a liver viable ex vivo using machine perfusion, outlining the essential conditions and key viability criteria during perfusion. The project's aim was to create a long‐term liver perfusion machine that mimics the body's core functions, offering an artificial environment as close as possible to natural in vivo physiological conditions. After a successful 5‐year development phase with porcine livers, the technology was then tested on two prototypes using human livers that were unsuitable for transplantation. This paper shares the experience, discoveries, and lessons learned during the research and development of a long‐term liver perfusion machine. It considers both the current state of the art and existing clinical practices in transplantation. The viability criteria are also discussed from the perspective of long‐term perfusion, especially since there's no current consensus in this area. Furthermore, the potential applications of these technologies are described. Overall, this long‐term perfusion technology is seen as a platform that could unlock exciting new clinical applications, offering significant patient benefits that may outweigh the economic challenges. Nevertheless, considerable research is still needed to bring these concepts and ideas into routine clinical practice.